Análisis al cumplimiento tributarío de un negocio ubicado en la ciudad de Guayaquil, dedicado a la comercialización de artículos de ferretería en general para el período fiscal 2008 - Valverde, P. (2009)
Taxes are the benefits that the State or an authorized public body to that effect, calls for economic subjects submitted to it. Such economic subjects come from a significant proportion of the population known as the Economically Active Population (PEA), who also are taxpayers for the reason of paying taxes. Since the taxes are the way to raise revenue, there is the Tax Law, which is the set of rules and principles of law relating to taxation, which governs all Taxes, Fees and Contributions in the country, without forgetting the Internal Tax Regime Organic Law. This work complies with current regulations and used in conjunction with the Ecuadorian Auditing Standards, to enable a proper analysis of tax compliance, for the tax period of the year 2008 of a trading company located in Guayaquil, dedicated to purchase and sale hardware goods in general.